The Dual‐Domain Porosity Apparatus: Characterizing Dual Porosity at the Sediment/Water Interface. Issue 4 (13th December 2018) - Scruggs, Courtney R.; Briggs, Martin; Day‐Lewis, Frederick D.; Werkema, Dale; Lane, John W.
Abstract: The characterization of pore‐space connectivity in porous media at the sediment/water interface is critical in understanding contaminant transport and reactive biogeochemical processes in zones of groundwater and surface‐water exchange. Previous in situ studies of dual‐domain (i.e., mobile/less‐mobile porosity) systems have been limited to solute tracer injections at scales of meters to hundreds of meters and subsequent numerical model parameterization using fluid concentration histories. Pairing fine‐scale (e.g., sub‐meter) geoelectrical measurements with fluid tracer data over time alleviates dependence on flowpath‐scale experiments, enabling spatially targeted characterization of shallow sediment/water interface media where biogeochemical reactivity is often high. The Dual‐Domain Porosity Apparatus is a field‐tested device capable of variable rate‐controlled downward flow experiments. The Dual‐Domain Porosity Apparatus facilitates inference of dual‐domain parameters, i.e., mobile/less‐mobile exchange rate coefficient and the ratio of less mobile to mobile porosity. The Dual‐Domain Porosity Apparatus experimental procedure uses water electrical conductivity as a conservative tracer of differential loading and flushing of pore spaces within the region of measurement. Variable injection rates permit the direct quantification of the flow‐dependence of dual‐domain parameters, which has been theorized for decades but remains challenging to assess using existing experimental methodologies. Abstract : Article impact statement : Introducing a novel instrument designed to study the exchange of solute between mobile and less‐mobile porosity (i.e., dual‐domain behavior) near the sediment/water interface.